JEWISH AND MUSLIM COMMUNICATION PATTERNS IN THE QUR'AN - Rohman, Baeti; Riam, Zainal; Badruddin; Amin, Muhammad (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2024)
Judaism and Islam are two religions that were revealed by Allah to humans, both religions are equipped with holy books as a guide for their people, the Torah is the Jewish holy book and the Qur'an is intended as the holy book of Islam, both the Torah and the Qur'an are the same contains the word of Allah SWT. The original Torah text had reported the arrival of the Prophet Muhammad, complete with his physical characteristics, but when Rasulullah was sent as a prophet, the Jews actually denied it because he did not come from the Children of Israel as the Jews hoped. The rejection of Muhammad as the last prophet was the source of tension in communication patterns between Jews and Muslims. This communication tension is getting stronger due to the actions of Jews who are trying to commit apostasy against Muslims because they feel that their religion is the truest. The Koran explicitly states that Jews will not be happy with Muslims until Muslims follow the path of the Jewish religion. The Qur'an also reminds us that the group that is most hostile to Muslims is the Jews, so Muslims need to be careful in establishing communication with Jews.